CONSERVATISM, CONSUMER ETHNOCENTRISM, VARIETY SEEKING, CONSUMER COSMOPOLITANISM, AND CULTURAL INTELLIGENCE AS DETERMINANTS OF PURCHASING FOREIGN LUXURY BRANDS - Zdravkovic, Stefan; Gašević, Dragana (The European Journal of Applied Economics, 2024)
Geopolitical tensions caused by the war in Ukraine, the migrant crisis, and economic instability are strengthening nationalist sentiments. Conservatism and consumer ethnocentrism are cohesive factors during crises, based on the principle that it is every citizen’s moral duty to protect the domestic economy by purchasing domestic products. Some citizens have cosmopolitan attitudes and are open to accepting ideas from other cultures. The aim of the research is to examine the impact of conservatism, consumer ethnocentrism, variety seeking, consumer cosmopolitanism, and cultural intelligence on consumers’ decision to purchase foreign luxury brands. The study was conducted in early 2024. in the territory of the Republic of Serbia. The total number of respondents in the sample was 511, and their responses were analyzed using SEM model within the statistical program SmartPLS 4. The results showed that conservatism has not statistically significant, while consumer ethnocentrism has a statistically significant negative impact on the purchase of luxury foreign brands. Variety seeking, consumer cosmopolitanism, and cultural intelligence have a positive and statistically significant impact on consumers’ decision to purchase foreign luxury brands. The research contributes by providing information that can be useful to managers in formulating marketing strategies for the market of the Republic of Serbia.